Resilience assessment of China's natural gas system under supply shortages: A system dynamics approach. (15th May 2022) - Ding, Yueting; Chen, Sai; Zheng, Yilei; Chai, Shanglei; Nie, Rui
Abstract: In recent years, with the rapid growth of natural gas (NG) consumption and foreign dependency in China, frequent supply shortages have threatened supply security. From the perspective of energy resilience, this paper aims to examine the recovery ability of China's NG system under supply shortages. By combining the resilience curve and system dynamics (SD) model, we proposed a resilience assessment framework. By SD modeling, this paper simulates and analyzes the system recovery process after supply shortages, and measures the resilience of the NG system based on the proposed framework. This paper also proposes the resilience elasticity index and identifies the key factors to improve the system resilience. The research conclusions mainly include: (1) system resilience can be improved by emergency supply measure and demand compression measure; (2) by currently available measures, the NG system can recover from a 30% import supply shortage, but not when seasonal demand peak happens at the same time; (3) transportation capacity of underground storage is the most important factor in improving NG system resilience; (4) underground reserve storage and its transportation capacity need to be improved simultaneously to guarantee the improvement of system resilience, but underground storage now lags behind pipelines at the present stage. Highlights: The resilience of China's natural gas system under supply shortages is explored; . A System Dynamics model and simulation analysis are used in the assessment of resilience. Keys to improving natural gas system resilience are identified.